Solid phase extraction and preconcentration of nickel in mineral waters with PAR-loaded amberlite XAD-7 and determination by flame atomic absorption spectrometry - Yaman, Mehmet; Ince, Muharrem (Atomic Spectroscopy Press Ltd, 2006)
A simple, sensitive, accurate, and selective method for the determination of ultratrace levels of nickel has been modified. The method is based on the preconcentration of nickel on PAR-loaded Amberlite XAD-7 at the pH range of 5.0-6.0 and a contact time as low as 45 minutes. The adsorbed nickel was eluted with concentrated nitric acid and measured by flame atomic absorption spectrometry (FAAS). Recoveries up to 90% were achieved. Sensitivity and reproducibility were examined considering the probability of chemical interferences in natural mineral waters where some metals are at levels higher than tap and natural surface waters. The optimized enrichment method was applied to the determination of nickel in various water samples. The detection limit was found to be 0.6 ng mL(-1). The relative standard deviation (RSD) was found to be 11% using 350 mL of 10 ng mL(-1) for 10 replicate enrichment procedures. Ni concentrations in the studied water samples were found to be ranging from 2.0-21 ng mL(-1).
Keywords: Trace-Metal Ions; Activated-Carbon; Natural-Water; Spectrophotometric Determination; Simultaneous Enrichment; Cobalt; Samples; Cadmium; Lead; Vegetables